Acetaminophen causes neurodevelopmental injury in susceptible babies and children: no valid rationale for controversy - Lisa Zhao; John P. Jones III; Lauren G. Anderson; Zacharoula Konsoula; Cynthia D. Nevison; Kathryn J. Reissner; William Parker (Clinical and Experimental Pediatrics, 2024)
Despite the worldwide acceptance of acetaminophen (APAP) as a necessary medicine in pediatrics, evidence that early exposure to APAP causes neurodevelopmental injury in susceptible babies and children has been mounting for over a decade. The evidence is diverse and includes extensive work with laboratory animals, otherwise unexplained associations, factors associated with APAP metabolism, and limited studies in humans. Although the evidence has reached an overwhelming level and was recently reviewed in detail, controversy persists. This narrative review evaluates some of that controversy. Evidence from the pre- and postpartum periods was considered to avoid controversy raised by consideration of only limited evidence of risks during the prepartum period. Among other issues, the association between APAP use and the prevalence of neurodevelopmental disorders was considered. A systematic review revealed that the use of APAP in the pediatric population was never tracked carefully; however, historical events that affected its use were documented and are sufficient to establish apparent correlations with changes in the prevalence of neurodevelopmental disorders. Moreover, problems with the exclusive reliance on results of meta-analyses of large datasets with limited time frames of drug exposure were reviewed. Furthermore, the evidence of why some children are susceptible to APAPinduced neurodevelopmental injuries was examined. We concluded that available evidence demonstrates that early exposure to APAP causes neurodevelopmental injury in susceptible babies and small children.